Prevalência ectoparasitária em tilápias do Nilo cultivadas em viveiros escavados na Região Oeste do Paraná - Schaedler, Adelaide Marina (2010)
To determine the prevalence of ectoparasites were examined Nile-tilapia, Oreochromis niloticus, cultured in ponds, in 20 termination fish farms on the municipalities of Assis Chateaubriand, Maripá, Marechal Cândido Rondon and Toledo including a nursery in Tupãssi on the western region of Paraná. One correlation between the presence of parasites and the final weights of the batches was held. The experimental period was nine months and 245 fishes were analyzed, the gills and integument was examined to search for the presence of ectoparasites. In the analysis, eight species of parasites were identified: Ichthyobodo necator, Ichthyophthirius multifiliis, Henneguya sp, tricodiníds, monogeneas, Epistylis sp., an Ergasilids and Nauplius copepod. The highest prevalence observed was tricodiníds in the three phases of fish development, fingerlings, juveniles and adults with values between 85.71% and 100%. The second highest prevalence were for monogeneas, with rates between 10.34% and 48%. Fingerlings and juveniles showed the highest prevalence rates for tricodiníds in the gills and Epistylis sp. in skin. The adult fishes were the most infested by other parasites, making gills the most parasitized structure by most respondents. The average weights were 497.2g on Assis Chateaubriand fishes, 510.5g for Maripá, 443.0g for Marechal Cândido Rondon and 379.3g for Toledo. The average temperatures during the fattening period significantly differed only in Assis Chateaubriand. The conclusion is that the prevalence and species of parasites found in this study have demonstrated no direct relationship with the average weight obtained in batches.